Information technology strategic plan for hospital using Ward and Peppard model - Muhammad Ismail Zabartih; Wijang Widhiarso (Goodwood Publishing, 2025)
Purpose: This study aims to identify IS/IT strategic plans, managerial activities, and operational activities in hospitals that can be used as proposals for IS/IT development in hospitals. Methodology/approach: The approach used in this research is the strategic planning of Ward and Peppard, who conduct an analysis of the internal and external environments at the hospital using various analytical tools such as SWOT, CSF, PEST, Value Chain, and McFarlan Strategic Grid. Results: The final result of this research is comprehensive strategic planning at the strategic, managerial, and operational levels, which are expected to be in line with the business objectives of the hospital. Conclusion: The findings highlight that systematic strategic planning enables hospitals to align IS/IT with organizational goals, improve efficiency, support decision-making, and enhance service quality. This approach ensures that IS/IT initiatives are not only technically feasible but also strategically sustainable in addressing the dynamic healthcare challenges. Limitations: The limitation of this research is the mapping of application proposals that are in accordance with the business objectives of hospitals. Contribution: The final result of this research can be used as a basis for developing IT at hospitals, which is expected to help in developing IT at hospitals in the future.